PENGARUH BIAYA PROMOSI DAN TARIF KAMAR TERHADAP PENDAPATAN PADA DISCOVERY KARTIKA PLAZA HOTEL - Kadek Sri Novi Arsini; Komang Krishna Yogantara; Ni Nyoman Sri Rahayu Trisna Dewi (Universitas Triatma Mulya, 2023)
The purpose of this study is to determine the Effect of Promotion Costs and Room Rates on Revenue at Discovery Kertika Plaza Hotel in 2016-2018 Before the Covid-19 Pandemic. The independent variables in this study are Promotional Cost (X1) and Room Rate (X2), the dependent variables in this study are Income (Y). This study used documentation data collection techniques. The population used in this study was the entire Income at Discovery Kartika Plaza Hotel in 2016-2018. This study used a saturated sampling technique, which used the entire population as a sample in the study. The analysis tool in this study uses multiple linear regression analysis to find out whether Promotional Costs and Room Rates have an effect on Revenue. The results of this study show the results that (1) Promotion Costs affect Revenue. (2) Room Rate affects Revenue.